Apixaban, a direct factor Xa inhibitor, inhibits tissue-factor induced human platelet aggregation in vitro: Comparison with direct inhibitors of factor VIIa, XIa and thrombin - Wong, Pancras C.; Jiang, Xiaosui (Thrombosis and Haemostasis, 2010)
Apixaban is an oral, direct and highly selective factor Xa (FXa) inhibitor in late-stage clinical development. This study evaluated the in vitro effect of apixaban on human platelet aggregation induced by thrombin derived via the extrinsic pathway. Direct inhibitors of FXa (rivaroxaban), FVIIa (BMS-593214), thrombin (dabigatran, argatroban) and FXIa (BMS-262084) were included for comparison. Citrated human plateletsrich plasma (PRP) was treated with 50 μg/ml corn trypsin inhibitor (to block the contact factor pathway) and 3 mM H-Gly-Pro-Arg- Pro-OH-AcOH (to prevent fibrin polymerisation). Human tissue factor (TF) (Innovin®; dilution 1:1,000 to 1:1,500) plus 7.5 mM CaCl2 was added to PRP pre-incubated with vehicle or increasing concentrations of inhibitors. The TF-induced platelet aggregation was measured by optical aggregometry. TF produced 85 ± 3% aggregation of human platelets in the vehicle-treated group (n=10). Apixaban and other factor inhibitors, except the FXIa inhibitor, inhibited TF-induced platelet aggregation with IC50 (nM) values as follows: 4 ± 1 (apixaban), 8 ± 2 (rivaroxaban), 13 ± 1 (BMS-593214), 46 ± 1 (dabigatran) and 79 ± 1 (argatroban). BMS-262084 (IC50 = 2.8 nM vs. human FXIa) had no effect on TF-induced platelet aggregation at 10 μM. These inhibitors at 10 μM had no effect on platelet aggregation induced by ADP and collagen, as expected from their mechanism of action. This study demonstrates that inhibition of thrombin generation by blocking upstream proteases (FVIIa and FXa) in the blood coagulation cascade is as effective as direct thrombin inhibition in preventing TF-induced platelet aggregation. Under these experimental conditions, a FXIa inhibitor did not prevent TF-induced platelet aggregation.
Keywords: Apixaban; dabigatran; direct factor Xa inhibitor; platelet aggregation; rivaroxaban; tissue factor